We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
63
2
avatar

r+pq=s-tq make q the subject

 Mar 12, 2019
 #1
avatar+101161 
+1

r + pq = s - tq       rearrange as

 

pq + tq  = s - r

 

q ( p + t )  =   s - r        divide both sides by p + t

 

q =   ( s - r)

       ______

        ( p + t)

 

cool coolcool

 Mar 12, 2019
 #2
avatar
0

thankscool

Guest Mar 12, 2019

3 Online Users

avatar